Right Ventricular Function Improves Early After Percutaneous Mitral Valve Repair in Patients Suffering From Severe Mitral Regurgitation - Neuser, Jonas; Buck, Hans Julian; Oldhafer, Maximiliane; Sieweke, Jan-Thorben; Bavendiek, Udo; Bauersachs, Johann; Widder, Julian D.; Berliner, Dominik (Frontiers in Cardiovascular Medicine, 2022)
Background Percutaneous mitral valve edge-to-edge procedure (PMVR) using the MitraClip® system (Abbot Vascular, CA) is an established therapy for severe mitral regurgitation (MR) in patients judged inoperable or at high surgical risk. Besides determining exercise capacity, right ventricular (RV) function has prognostic value in heart failure and after cardiac surgery. We therefore investigated the impact of PMVR on RV function in patients with severe MR. Methods and Results Sixty-three patients undergoing PMVR at our department were prospectively enrolled. Transthoracic echocardiography was performed before, early (2–12d) after PMVR and after 3 months, including advanced echocardiographic analyses such as 3D imaging and strain analyses. At baseline, all patients presented with advanced heart failure symptoms. Etiology of MR was more often secondary and, if present, left ventricular (LV) dysfunction was predominantly caused by ischemic cardiomyopathy. PMVR substantially reduced MR to a grade ≤ 2 in most patients. Echocardiographic assessment revealed a largely unchanged LV systolic function early after PMVR, while in contrast RV function substantially improved after PMVR [3D RV EF (%): pre 33.7% [27.4; 39.6], post 40.0% [34.5; 46.0] (p < 0.01 vs. pre), 3 months 42.8% [38.3; 48.1] (p < 0.01 vs. pre); 2D RV GLS (%): pre −12.9% [−14.5; −10.5], post −16.0% [−17.9; −12.6] (p < 0.01 vs. pre), 3 months −17.2% [−21.7; −14.9] (p < 0.01 vs. pre)]. Factors that attenuated RV improvement were larger ventricular volumes, lower LV function, secondary MR, and a higher STS score (all p < 0.05). Conclusion By using advanced echocardiographic parameters, we discovered an early improvement of RV function after PMVR that is preserved for months, independent from changes in LV function. Improvement of RV function was less pronounced in patients presenting with an advanced stage of heart failure and a higher burden of comorbidities reflected by the STS score.